Ethylene Production Affects Blueberry Fruit Texture and Storability - Farneti, Brian; Khomenko, Iuliia; Ajelli, Matteo; Emanuelli, Francesco; Biasioli, Franco; Giongo, Lara (Frontiers in Plant Science, 2022)
Ethylene, produced endogenously by plants and their organs, can induce a wide array of physiological responses even at very low concentrations. Nevertheless, the role of ethylene in regulating blueberry (Vaccinium spp) ripening and storability is still unclear although a peak in ethylene production has been observed in several studies during blueberry ripening. To overcome this issue, we evaluate the endogenous ethylene production of a Vaccinium germplasm selection at different fruit ripening stages and after cold storage, considering also textural modifications. Ethylene and texture were further assessed also on a bi-parental full-sib population of 124 accessions obtained by the crossing between ‘Draper’ and ‘Biloxi’, two cultivars respectively characterized by a high and low chill requirement. Our results were compared with an extensive literature research, carried out to collect all accessible information on published works related to Vaccinium ethylene production and sensitivity. Results revealed a high variability in ethylene production among genotypes. These differences in ethylene production are related with blueberry fruit storage performances based on textural alterations. Specifically, blueberry accessions characterized by the highest ethylene production show a more severe texture decay during storage. Our results support the possibility of tailoring ad hoc preharvest and postharvest strategies to extend blueberry shelf life and quality according with the endogenous ethylene production level of each cultivar.